Overcriminalization in the Modern Criminal Justice System: A Threat to the Principles of Legality and Substantive Justice: Overcriminalization in the Modern Criminal Justice System: A Threat to the Principles of Legality and Substantive Justice - Agus Kelana Putra; Kristiawanto Kristiawanto; Sineenart Suasoongnern (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
Overcriminalization has become a systemic problem in modern legal systems, characterized by a tendency to use criminal law excessively to regulate various social behaviors. This study critically examines how the expansion of criminal law—both in scope and intensity—can threaten the principle of legality and undermine substantive justice. Using a normative qualitative approach, this study applies doctrinal and comparative legal analysis to three jurisdictions: Indonesia, the United States, and Germany. Primary sources include legislation and court decisions, while secondary data is obtained from academic literature and institutional reports. The findings reveal that overcriminalization often results in vague legal norms, disproportionate sanctions, and selective law enforcement—particularly affecting vulnerable groups. The study reveals that this trend has eroded legal certainty and turned criminal law into a political and moral tool. By integrating penal minimalism theory, justice theory, and legal positivism, this article offers normative parameters in the form of necessity, proportionality, and the principle of ultimum remedium to recalibrate the boundaries of legitimate criminalization. This research contributes to contemporary academic discourse by providing a structured analytical framework and concrete policy recommendations to strengthen the legitimacy and fairness of the modern criminal justice system.